MicroRNA‐495‐3p functions as a tumor suppressor by regulating multiple epigenetic modifiers in gastric carcinogenesis. Issue 1 (27th November 2017) - Eun, Jung Woo; Kim, Hyung Seok; Shen, Qingyu; Yang, Hee Doo; Kim, Sang Yean; Yoon, Jung Hwan; Park, Won Sang; Lee, Jung Young; Nam, Suk Woo
Abstract: MicroRNAs (miRNAs) engage in complex interactions with the machinery that controls the transcriptome and concurrently target multiple mRNAs. Here, we demonstrate that microRNA‐495‐3p (miR‐495‐3p) functions as a potent tumor suppressor by governing ten oncogenic epigenetic modifiers (EMs) in gastric carcinogenesis. From the large cohort transcriptome datasets of gastric cancer (GC) patients available from The Cancer Genome Atlas (TCGA) and the National Center for Biotechnology Information (NCBI) Gene Expression Omnibus (GEO), we were able to recapitulate 15 EMs as significantly overexpressed in GC among the 51 EMs that were previously reported to be involved in cancer progression. Computational target prediction yielded miR‐495‐3p, which targets as many as ten of the 15 candidate oncogenic EMs. Ectopic expression of miRNA mimics in GC cells caused miR‐495‐3p to suppress ten EMs, and inhibited tumor cell growth and proliferation via caspase‐dependent and caspase‐independent cell death processing. In addition, in vitro metastasis assays showed that miR‐495‐3p plays a role in the metastatic behavior of GC cells by regulating SLUG, vimentin, and N‐cadherin. Furthermore, treatment of GC cells with 5‐aza‐2'‐deoxcytidine restored miR‐495‐3p expression; sequence analysis revealed hypermethylation of the miR‐495‐3p promoter region in GC cells. A negative regulatory loop is proposed, whereby DNMT1, among ten oncogenic EMs, regulates miR‐495‐3p expression via hypermethylation of the miR‐495‐3p promoter. Our findings suggest that the functional loss or suppression of miR‐495‐3p triggers overexpression of multiple oncogenic EMs, and thereby contributes to malignant transformation and growth of gastric epithelial cells. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.